Revealing Stereotypes: Evidence from Immigrants in Schools - Alberto Alesina; Michela Carlana; Eliana La Ferrara; Paolo Pinotti (Institute of Labor Economics (IZA), 2018)
If individuals become aware of their stereotypes, do they change their behavior? We study this question in the context of teachers' bias in grading immigrants and native children in middle schools. Teachers give lower grades to immigrant students compared to natives who have the same performance on standardized, blindly-graded tests. We then relate differences in grading to teachers' stereotypes, elicited through an Implicit Association Test (IAT). We find that math teachers with stronger stereotypes give lower grades to immigrants compared to natives with the same performance. Literature teachers do not differentially grade immigrants based on their own stereotypes. Finally, we share teachers' own IAT score with them, randomizing the timing of disclosure around the date on which they assign term grades. All teachers informed of their stereotypes before term grading increase grades assigned to immigrants. Revealing stereotypes may be a powerful intervention to decrease discrimination, but it may also induce a reaction from individuals who were not acting in a biased way.
Keywords: I24; J15; 330; immigrants; teachers; implicit stereotypes; IAT; bias in grading